PENGARUH PROMOSI DAN PELAYANAN UNTUK KEPUTUSAN PEMBELIAN JASA - Aldhiansyah Egy Pramanto; Burhan Stafrezar (PUTRA JAWA PUBLISHER, 2023)
In today's modern era, many businesses are opening shops in the field of shoe washing services, especially in big cities. The research conducted by the author aims to see whether or not there is influence of promotion and service in making decisions to purchase shoe washing services. The sample used in this study amounted to 30 customers purchasing services. This study utilized a qualitative approach by conducting several face-to-face interviews. The results of the study show that all statement items are stated in a narrative, valid and also reliable manner.